Drops like stars - Bell, Rob, 1970- (Grand Rapids, Mich. : Zondervan, 2009)
This book is an exploration of the complex relationship between suffering andcreativity, driven by the belief that there is art in the agony.
The art of disruption -- The art of honesty -- The art of the ache -- The art of solidarity -- The art of elimination -- The art of failure.
Includes bibliographical references.
Keywords: Suffering -- Religious aspects -- Christianity; Creation (Literary, artistic, etc.) -- Religious aspects -- Christianity